Desenvolvimento de um programa computacional livre, gráfico, e multiplataforma para analisar sistemas elétricos de potência em regime permanente e dinâmico - Oliveira, Thales Lima (2019)
As regards to the computational analysis of power systems, several commercial and non-commercial simulators were developed, capable of performing several calculations through mathematical modeling of the components of a power grid. Commercial software, usually not free, makes it impossible to insert and customize new tools by possessing the closed code, protected by proprietary licenses. As opposed to private programs, the concept of free and open-source software was born, which promotes unrestricted access to information, including the source code. Some open-source applications have been created in the area of electrical power systems, but there are some shortcomings in these programs, such as the lack of a graphical user interface (GUI), CAD tools, dependence on proprietary software and operating systems, besides the discontinuation in development. Within this context, the development of the PSP-UFU (Power Systems Platform of the Federal University of Uberlândia) was started, capable of performing, for numerous types of power systems, four studies: load flow, short-circuit, harmonics and stability. This platform has an open-source and advanced graphical interface with CAD tools, allowing the construction of any electrical network and control systems through the manipulation of visual elements. It also stands out its multiplatform nature, making it independent of a single operating system. Such features are unprecedented in open-source programs for power systems. To validate the calculation tools developed, test systems were carried out and the results from PSP-UFU were compared with those originated from Anarede, Anafas, HarmZs Anatem, and MATLAB/Simulink, which are well-established programs. The comparative results proved to be very good, attesting to the PSP-UFU as a software capable of assisting research and education areas as well as practical engineering applications.